Implementation of the Consensusual Principle of Financing Agreements at BPRS Buana Mitra Perwira Purbalingga - Anggita Isty Intansari; Sulasih (Universitas Amikom Purwokerto, 2025)
Agreement can take two forms: written and unwritten (oral). Both forms are binding, provided they meet the requirements stipulated in Article 1320 of the Civil Code, namely, the existence of an agreement. The principle of consensualism is reflected in the agreement made between the parties, which is described as a statement of free will approved by the parties. BPRS Buana Mitra Perwira is a Sharia financial institution that engages in fundraising and distribution of funds, which involves direct or written agreements. This study aims to examine the implementation of the principle of consensualism in the agreements applied by BPRS Buana Mitra Perwira Purbalingga. The research employs a sociological juridical approach, involving field activities to gather real-world data, making it a case study. The study uses a descriptive approach, with data collection methods including in-depth interviews, participant observation, and documentation. The sampling technique used is purposive sampling and snowball sampling. The results of the study show that the principle of consensualism is applied in the financing agreements of BPRS Buana Mitra Perwira Purbalingga, which take the form of consumptive financing (sale and purchase, such as murabahah, IMBT, or istisna') and productive financing (cooperation, such as mudharabah or musyarokah). The agreement draft is typically prepared by BPRS Buana Mitra Perwira, and customers only need to read and sign the agreement based on their agreement.